Digital drinking water reminder using arduino and Blynk’s application: an innovation - Mohd Hashim, Mohamad Hisyam; Samsunahar, N. (Penerbit UTHM, 2020)
This project had been produced because the product would be able to help a person who often forget to drink enough water in their daily life cause of too busy with various jobs. Lack of water in the body can cause a person to become dehydrated. With unpredictable weather nowadays; a person does not realize that they are actually dehydrated. Therefore, Digital Drinking Water Reminder using Arduino and Blynk’s application was developed to help remind consumers to always drink up to eight glasses of water a day . This product has control over the application with Blynk notification that had been sent from Arduino ESP8622 (wifi module). The SDLC models had been chosen as a development model which included six phases.. The six phases are planning, analysis, design, process for making, testing and integration and maintenance. The project design was developed using Fritzing software to designed the circuit of Digital Drinking Water Reminder. Testing was done to ensure that the coding was made to act as planned. The project also involves specialist confirmation of three members, such as a pharmacist, a doctor, and a gym trainer. Overall, the product Digital Drinking Water Reminder is working and achieving the objectives.